Spatial variability of biomass and soil microbial activity under crop-livestock-forest integration system - de Souza, Paulino Taveira [UNESP]; Silva, Tatiane Carla [UNESP]; Troleis, Maria Júlia Betiolo [UNESP]; Sena, Karla Nascimento [UNESP]; Silva, Anne Caroline Rocha [UNESP]; Dos Santos, Talles Eduardo Borges; Montanari, Rafael [UNESP] (Universidade Federal de Santa Maria, 2021)
Soil quality refers to the assessment of the chemical, physical and biological properties of the soil and has been a subject explored within the lines of agronomic research because of anthropic actions that often cause degradation. The objective was to research, among the studied physical and biological attributes, those that best explain, linearly and spatially, the variability of the soil cultivated with soybeans in the rainy season and fallow in the dry season in the agrosilvopastoral system. The work was carried out in the 2015/2016 agricultural year, in Ipameri, Goiás. The spatial distributions and correlations between some soil quality indicator attributes were analyzed: microbial biomass carbon (CBM), soil microbial respiration (C-CO2), metabolic quotient (qCO2) and soil moisture (UG), at a depth of 0.00-0.10 m, during periods of rain and drought. A geostatistical grid was installed, where 52 points were collected. Descriptive analysis of the data was carried out to obtain linear, simple and multiple correlations between the attributes. The semivariograms were modeled to obtain the respective krigings and cross-validations. The co-krigages of interest were established. The microbiological attributes of the soil were good indicators of specific management zones, showing greater spatial dependence in the rainy season. qCO2 was directly related to C-CO2 in the rainy season, while CBM was inversely proportional in bothrainy and dry periods. The qCO2 was the attribute that best represented, linearly and spatially, the variability of the soil under the ILPF system, reflecting the zones of greatest efficiency in the use of the substrate by soil organisms.
Variabilidade espacial da biomassa e atividade microbiana do solo sob sistema de integração lavoura-pecuária-floresta
Keywords: Geoestatistics; Microbial biomass carbon; Soil microorganisms; Soil quality